Pengaruh Kerjasama Guru PAI dengan Orang tua Terhadap Kemampuan Membaca Al-Qur’an Siswa di SMP - amarafebrian (Jurnal Pendidikan Guru Profesional, 2025)
This study aims to determine the influence of cooperation between Islamic Education (PAI) teachers and parents on the Qur’an reading ability of seventh-grade students at SMP Negeri 3 Purbalingga. The background of this research is based on the importance of collaboration between PAI teachers and parents in supporting religious learning, particularly in developing students’ Qur’an reading skills. However, in reality, there are still students whose reading abilities have not reached the expected level. This condition is presumed to result from the suboptimal cooperation between teachers and parents in guiding students both at school and at home. This research employed a quantitative correlational approach involving two variables: cooperation between PAI teachers and parents as the independent variable (X), and students’ Qur’an reading ability as the dependent variable (Y). Data were collected through questionnaires and documentation of Qur’an learning scores. The population consisted of 210 seventh-grade students, while the sample included 89 students selected randomly from an initial 138 respondents. Data analysis was conducted using the Rank Spearman correlation test, both manually and with the help of SPSS version 22. The results showed a positive but weak relationship between teacher–parent cooperation and students’ Qur’an reading ability, with a correlation coefficient (r) of 0.168 and a significance value (p) of 0.048 (p < 0.05). This indicates that the better the cooperation between PAI teachers and parents, the higher the students’ Qur’an reading ability tends to be, although the influence is not strong. Therefore, this study highlights the importance of collaborative efforts between schools and families through effective communication and continuous guidance to enhance students’ Qur’an reading proficiency.